PASSING THE POISONED CHALICE: JUDICIAL NOTICE OF GENOCIDE BY THE ICTR - Shannon, Kirk (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2006)
Relying on the procedural mechanism of judicial notice, the Appeals Chamber of the United Nations International Criminal Tribunal for Rwanda (ICTR) released a decision in the Prosecutor v. Karemera case that relieves the prosecution of the burden of producing evidence proving that the horrific events in Rwanda meet the legal requirements of genocide. This paper traces the origins and development of the doctrine of judicial notice in international criminal law so as to examine the Appeals Chamber’s decision and its implications. Traditionally, facts that go to legal conclusions or to the elements of the crime with which the accused is charged have been deemed prohibited subjects for this efficiency-producing mechanism. Because a finding of genocide is a legal conclusion, the author argues that judicial notice of genocide violates the procedural rights of the accused by barring defence submissions on the definition of this legal conclusion. The author continues by arguing that the Appeals Chamber has violated the substantive rights of the accused by pushing the doctrine of judicial notice beyond its proper limits and thereby shrinking the protections afforded by the fundamental rights enshrined in the Tribunal’s Statute. While it is imperative that the Tribunal punish the perpetrators of the heinous crimes committed in Rwanda, it is nonetheless essential that the ICTR conduct proceedings in a manner that safeguards the procedural and substantive rights of the accused. To this end, the author suggests other means by which the Tribunal could have promoted efficiency and justice without violating the rights of the accused.